Joint Trajectories of Physical Activity and Depressive Symptoms in Postmenopausal Women in China: A Group-Based Dual Trajectory Analysis of the Five-Year Longitudinal Study - Shi Y; Guo H; Tian R; Zhang N; Wang C; Liu W; Duan Z (Journal of Multidisciplinary Healthcare)
Yan Shi,1,2 Huaqing Guo,1 Ruonan Tian,1 Nan Zhang,3 Chen Wang,1 Weiliang Liu,4 Zhiguang Duan1 1School of Humanities and Social Sciences, Shanxi Medical University, Taiyuan, Shanxi, People’s Republic of China; 2School of Public Health, Changzhi Medical College, Changzhi, Shanxi, People’s Republic of China; 3School of Management, Shanxi Medical University, Taiyuan, Shanxi, People’s Republic of China; 4The First Affiliated Hospital of Xi’an Medical University, Xian, Shaanxi, People’s Republic of ChinaCorrespondence: Zhiguang Duan, School of Humanities and Social Sciences, Shanxi Medical University, Taiyuan, Shanxi, 130001, People’s Republic of China, Email 15534493161@163.comObjective: The trajectories of the associations of physical activity (PA) with depressive symptoms in postmenopausal women are still unclear. This study aimed to identify the joint trajectories of PA and depressive symptoms over a 5-year period among Chinese postmenopausal women and to comprehensively examine their associations and predictors.Methods: The study included 1303 postmenopausal women who participated in the China Health and Retirement Longitudinal Survey (CHARLS) between 2015, 2018 and 2020. Depressive symptoms were measured by CESD-10. PA was assessed by the IPAQ-SF. Group-based dual trajectory modeling (GBDTM) was applied to examine the joint trajectories of PA and depressive symptoms in postmenopausal women. Quantile regression assessed their associations within trajectory groups, and a multinomial logistic model identified group predictors.Results: Three distinct dual trajectories of PA and depressive symptoms were identified in postmenopausal women: moderate stable-low increase (32.0%), high curve-moderate increase (46.1%), and low stable-high increase (21.9%), all showing a worsening trend in depressive symptoms. Consistent moderate PA was accompanied by low slightly increased depressive symptoms. Low PA was positively associated with high depressive symptoms in the 10th and 30th quantiles. High PA initially suppressed depressive symptoms, but its inhibitory effect diminished as symptoms worsened. Predictors of latent trajectory groups included rural residence, uneducated, insufficient sleep, and comorbidities.Conclusion: Screening for depressive symptoms in postmenopausal women is necessary, especially in those with long-term low PA. PA interventions should be tailored according to the severity and trajectory of depressive symptoms.Keywords: depressive symptoms, physical activity, postmenopausal women, dual trajectories, longitudinal study